Secretion of placental peptide hormones: functions and trafficking - Ahmadi, Sadia M.; Perez, Maira L.; Guardia, Carlos M. (Frontiers in Endocrinology, 2025)
The placenta is a dynamic endocrine organ that plays a crucial role in fetal development by secreting a diverse array of peptide hormones that regulate maternal and fetal physiology. These hormones, including human chorionic gonadotropin (hCG), human placental lactogen (hPL), and placental growth hormone (hPGH), among others, are essential for pregnancy maintenance, fetal growth, and metabolic adaptation. Dysregulation of the secretory machinery and the levels of these hormones in circulation is associated with a myriad of pregnancy-related disorders. Despite their significance, the mechanisms governing their intracellular trafficking and secretion remain incompletely understood. This review synthesizes current knowledge on the secretion pathways of placental hormones, highlighting the interplay between constitutive and regulated secretion, and the challenges in defining these mechanisms due to the unique structure of the syncytiotrophoblast. We also discuss how emerging technologies, such as 2D and 3D placental models and advanced protein trafficking assays, can provide deeper insights into the regulation of placental hormone secretion. Understanding these processes will not only enhance our knowledge of placental biology but also provide new avenues for diagnosing and treating pregnancy-related disorders.